How to practice vocabulary with large classes in elemntary school - Argudo Matute, Elizabeth Tatiana; Avedaño Saquisilí, Diego Leonardo
Due to the fact that many teachers nowadays face the problem of teaching large classes without having enough resources, we decided to do a research to help this weakness in our education. In our research, we tried to gather some ideas to make a collection of activities using flashcards, songs, and games that could be applied in large classes which have little resources. First, we did an investigation about the theory on which our work was based. We researched about teaching children, teaching vocabulary, and managing large classes. Second, we carried out a field research. We interviewed an expert and applied a survey to students from seventh grade from a ?fiscomissional? elementary school of Cuenca. The ideas, product of the literature review and the field research, were used to gather activities to practice vocabulary with large groups. As a conclusion, we can say that this topic was viable since we got all the information to proof that is it possible to practice vocabulary with large classes using the appropriate techniques and resources.